Education scolaire, performance et equite sociale: des relations problematiques - Lenoir, Yves (Linguarum Arena, 2018)
Using critical theory, this paper first confronts critically the relationship between education and performance in light of globalisation and its underlying neo‑liberal ideology. This comparison reveals that there is a definite compatibility between them, but it is fully slanted towards efficiency logic and human capital production. Then, adopting a critical attitude, the paper questions this direction, in the name of the emancipation and citizenship prospects, which brought the school system reorganisation by democratic nation‑states. The current choices have distorted these objectives and have redirected them towards utilitarian learnings and an increasingly therapeutic socialisation. Finally, the paper stresses the inseparability between the performance issue, the social equity issue and the education/teaching effectiveness issue in order to highlight the need for taking into account qualitative dimensions, which stem from the background and the pupils, so as to focus much more on learning processes, rather than on learning outcomes themselves.